Systematic analysis of monoterpenes: Advances and challenges in the treatment of peptic ulcer diseases - Périco, Larissa Lucena [UNESP]; Emílio-Silva, Maycon Tavares [UNESP]; Ohara, Rie [UNESP]; Rodrigues, Vinícius Peixoto [UNESP]; Bueno, Gabriela [UNESP]; Barbosa-Filho, José Maria; da Rocha, Lúcia Regina Machado [UNESP]; Batista, Leônia Maria; Hiruma-Lima, Clélia Akiko [UNESP] (MDPI, 2020)
Peptic ulcer disease (PUD) is a multifactorial and complex disease caused by an imbalance of protective and aggressive factors (endogenous and exogenous). Despite advances in recent years, it is still responsible for substantial mortality and triggering clinical problems. Over the last decades, the understanding of PUD has changed a lot with the discovery of Helicobacter pylori infection. However, this disease continues to be a challenge due to side-effects, incidence of relapse from use of various anti-ulcer medicines, and the rapid appearance of antimicrobial resistance with current H. pylori therapies. Consequently, there is the need to identify more effective and safe anti-ulcer agents. The search for new therapies with natural products is a viable alternative and has been encouraged. The literature reports the importance of monoterpenes based on the extensive pharmacological action of this class, including wound healing and anti-ulcerogenic agents. In the present study, 20 monoterpenes with anti-ulcerogenic properties were evaluated by assessing recent in vitro and in vivo studies. Here, we review the anti-ulcer effects of monoterpenes against ulcerogenic factors such as ethanol, nonsteroidal anti-inflammatory drugs (NSAIDs), and Helicobacter pylori, highlighting challenges in the field.
Keywords: Anti-ulcer agent; Helicobacter pylori; Monoterpenes; Peptic ulcer disease